Dynamics and Prospects of the Indonesian Halal Industry: A Comprehensive Analysis Based on Policy, Supply Chain, and Sharia Economics Towards a Global Halal Hub - Linggawijaya, Hisyam Armana (Riviera Publishing, 2025)
This study analyzes the dynamics and prospects of the halal industry in Indonesia, highlighting the shift in global consumption toward a values-based lifestyle. Indonesia, as the largest halal consumer, faces a paradox: massive consumption (projected at US282 billion by 2025) while global production lags behind. This study aims to analyze consumption, the role of the sharia economy, the effectiveness of government policies, halal supply chain management, and the challenges and opportunities for Indonesia to become a global halal hub. Using a systematic literature review of indexed journals and government documents (Law 33/2014, Government Regulation 42/2024), this study finds that increased consumption is driven by government preference and support. The sharia economy contributes through principles of fairness and financial instruments. Government policies, particularly mandatory certification by BPJPH, LPH, BSN, and KNEKS, strengthen infrastructure. The halal supply chain is crucial but is hampered by costs and understanding among MSMEs. Challenges include low awareness, suboptimal human resources, local competitiveness, a consumerist mentality, MSME certification costs, limited infrastructure, global competition, and a lack of international standardization. Significant opportunities come from the domestic market, government commitment, strong development pillars, digitalization, and the ambition to become a global halal hub. This research bridges the gap between high consumption and low production, offering strategic perspectives for Indonesia to become a leading global halal producer and hub.